2023
DOI: 10.3390/ijpb14030044
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Most Effective Media for Bioprospecting Three Indigenous Freshwater Microalgae Species

Abstract: Microalgae are a natural source of lipids, carotenoids, and other value-added compounds. The combination of nutrients and their precise ratio have a significant impact on the productivity of microalgae-mediated compounds. The biomass, lipid, chlorophyll, and carotenoid production of three microalgae species, namely, Monoraphidium sp., Chlorella sorokiniana, and Scenedesmus obliquus, were investigated by employing standard photoautotrophic media, namely, BG-11, BBM, and HS CHU-10. BBM was found as the most effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The choice of culture media was based on a comparative study of three different media: BG-11, BBM, and HS CHU-10. The study revealed that BBM was the most suitable and effective medium for cultivating S. obliquus , making it the optimal choice for this research (Yadav et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The choice of culture media was based on a comparative study of three different media: BG-11, BBM, and HS CHU-10. The study revealed that BBM was the most suitable and effective medium for cultivating S. obliquus , making it the optimal choice for this research (Yadav et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…23 Similarly, the biomass concentration of S. obliquus in HE was higher than the value reported for S. obliquus grown in BG-11, BBM, and HS CHU-10 media. 41 These results suggest that the HE can provide a favourable growth environment for microalgae, leading to enhanced biomass productivity compared to commonly used growth media.…”
Section: Resultsmentioning
confidence: 89%
“…The cell suspensions of Isochrysis galbana without hormone treatment (control) and cultures treated with hormones were harvested and subsequently centrifuged at 8000 rpm for 5 min. Pellets were resuspended in PBS buffer (Yadav et al 2023a). Nile red (9-diethylamino-5Hbenzo [α] phenoxazine-5-one) staining was performed 15 min before imaging to detect the presence of lipid by adding 380 µL of microalgal suspension to 20 µL of Nile red (Sigma; stock solution of 0.2 mg/mL in DMSO).…”
Section: Morphological Data Acquisitionmentioning
confidence: 99%